STEM e-worksheet innovation: Encouraging collaboration in excretory system learning - Minatani, Anisa; Supriyatin, Supriyatin; Rusdi, Rusdi (Universitas Negeri Jakarta, 2025)
Excessive use of gadgets leads to individualism and less exploration and thinking among students due to the easiness offered by the gadgets. Moreover, students have low collaboration skills so that less able to cooperate. The study aims to produce a STEM-based e-LKPD in the Excretory System that is effective in enhancing students’ collaboration skills. The research method used is Educational Design Research with Hannafin Peck model. Data collection is conducted through a need analysis questionnaire to students and interviews with teachers. The development of the STEM-based e-LKPD uses Canva and Flipbook. Media and content experts work on the feasibility test of the product. Product trials are conducted on small groups of 15 students, large groups of 32 students, and educators. The effectiveness test employs the control group pre-test and post-test design using an instrument consisting of 8 questions on collaboration skills. The MANOVA test indicates a Pillai’s Trace value is smaller than 0.05 suggesting a significant difference between compared groups. The average N-gain of collaboration skills is 71.36. The results can be concluded that the STEM-based e-LKPD is effective in improving collaboration skills.